2021
DOI: 10.1080/10255842.2021.1984434
|View full text |Cite
|
Sign up to set email alerts
|

Modelling uptake and transport of therapeutic agents through the lymphatic system

Abstract: The ability of the lymphatic network to absorb large molecules and bypass the first-pass liver metabolism makes it appealing as a delivery system for therapeutic substances. In most cases, the drug is injected into the subcutaneous tissue and must negotiate the tissue space, before being drained via the lymphatics. Tracking the transport of drug molecules through this route is challenging, and computational models of lymphatic drainage can play an important role in assessing the efficacy of a proposed delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…Han et al ( 2023a ) showed that lymphatic uptake following subcutaneous administration significantly affects macroscopic drug absorption. They also found that the injection depth does not affect lymphatic uptake, which contrasts with the findings of Jayathungage Don et al ( 2021 ). Following this, Han et al ( 2023b ) later improved their transport model to investigate the effects of the drug radius.…”
Section: Existing Computational Models Of the Lymphaticscontrasting
confidence: 64%
See 4 more Smart Citations
“…Han et al ( 2023a ) showed that lymphatic uptake following subcutaneous administration significantly affects macroscopic drug absorption. They also found that the injection depth does not affect lymphatic uptake, which contrasts with the findings of Jayathungage Don et al ( 2021 ). Following this, Han et al ( 2023b ) later improved their transport model to investigate the effects of the drug radius.…”
Section: Existing Computational Models Of the Lymphaticscontrasting
confidence: 64%
“…Some models spanned multiple components of the lymphatic system, while many focused on a single component, such as the collecting vessels. For example, Bertram et al ( 2011 ) focused on the larger collecting vessels to understand the pumping mechanism of lymphangions, while Ikhimwin et al ( 2020 ) and Jayathungage Don et al ( 2021 ) considered multiple parts of the lymphatic system to understand the drainage through the lymphatic vessel network hierarchy. Some studies reviewed key aspects of lymphatic physiology to consider in computational modeling approaches, such as Munn ( 2015 ), who summarised mechanobiological control mechanisms in the lymphatic vessels.…”
Section: Existing Computational Models Of the Lymphaticsmentioning
confidence: 99%
See 3 more Smart Citations